What Still Needs to be Noted: Pseudo-Clefts in the Academic Discourse of Applied Linguistics - Zhou, Hui; Chen, Ming (Frontiers in Psychology, 2021)
Pseudo-clefts are the building blocks of coherent discourse progression and serve as a rhetorical toolkit to construct an authorial stance in the academic discourse. Despite an increasing interest in grammatical constructions in the academic discourse, researchers have not treated pseudo-clefts in much detail. This paper explores the features of pseudo-clefts in the corpus of academic discourse in the field of applied linguistics. Here, we take the textual and the interpersonal perspectives, focusing on the use of pseudo-clefts in terms of their distribution in generic structure, discourse functions with reference to clefted constituents, and evaluative meaning. The results show that pseudo-clefts were more frequently used in “Results and Discussion” and Literature Review, performing the functions such as the specification of key terms, generalization of the literature, the description and explanation of findings, etc. They are facilitative in creating information gaps and establishing a logic-semantic expansive relationship between the clauses. The findings also suggest that the pseudo-clefts are evaluative devices and are involved in the construction of authorial identities.